2015
DOI: 10.1371/journal.pone.0142548
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and Protective Efficacy of Brugia malayi Heavy Chain Myosin as Homologous DNA, Protein and Heterologous DNA/Protein Prime Boost Vaccine in Rodent Model

Abstract: We earlier demonstrated the immunoprophylactic efficacy of recombinant heavy chain myosin (Bm-Myo) of Brugia malayi (B. malayi) in rodent models. In the current study, further attempts have been made to improve this efficacy by employing alternate approaches such as homologous DNA (pcD-Myo) and heterologous DNA/protein prime boost (pcD-Myo+Bm-Myo) in BALB/c mouse model. The gene bm-myo was cloned in a mammalian expression vector pcDNA 3.1(+) and protein expression was confirmed in mammalian Vero cell line. A s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…In this study, the designed vaccine construct is about 51 kDa. The pcDNA3.1 has been exhibited high efficacy for in vivo expression of different recombinant proteins with different sizes from 14 to 73 kDa [98] , [99] , [100] . Also, high expression of recombinant proteins with sizes ranged from 14 to 51 kDa have been reported for pET-28a vector [101] , [102] .…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the designed vaccine construct is about 51 kDa. The pcDNA3.1 has been exhibited high efficacy for in vivo expression of different recombinant proteins with different sizes from 14 to 73 kDa [98] , [99] , [100] . Also, high expression of recombinant proteins with sizes ranged from 14 to 51 kDa have been reported for pET-28a vector [101] , [102] .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, to further enhance the protective efficacy of earlier identified Bm-Myo, we cloned Bm-Myo in mammalian expression vector and used this plasmid construct (DNA vaccine) to immunize BALB/c mice with homologous DNA as well as DNA/protein prime boost which demonstrated better protection than when recombinant myosin was employed [21]. Findings also demonstrated that priming with DNA construct followed by protein boosters elicited more robust humoral and cellular immune responses and provided higher rate of protection against L3 in the peritoneal cavity of mice than when DNA vaccination was followed by DNA vaccine booster.…”
Section: Discussionmentioning
confidence: 99%
“…The recombinant plasmid pcDNA3.1-Myo (Myo-pcD) was constructed as described earlier [21]. In brief, bm-myo (accession number AY705730) gene was cloned in mammalian expression vector pcDNA 3.1(+) (Invitrogen, USA) at BamHI/XhoI restriction sites and plasmid was isolated by Endo-free plasmid isolation kit (Qiagen, Germany) for immunizing M .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in TCR transgenic mice have also shown that the O. volvulus antigens O v ALT-2 and O v NLT-1 exert suppressive effects on CD8 + T cell proliferation and cytokine release ( 37 ). Recently, heterologous prime-boost vaccination administration of B. malayi heavy chain myosin induced enhanced CD8 + T cell expansion in mouse spleen ( 38 ). Although CD8 + T cell levels are elevated during filarial infections, it may be that CD8 + T cell-mediated immunity is most relevant at the initial stages of the infections when the parasite is establishing itself in the host.…”
Section: Cd8 + T Cells In Anti-filarial Immunitymentioning
confidence: 99%